O Canto Coral na Comunidade Cristã: reflexões e conclusões a partir de uma pesquisa social - Lichtler, André Daniel (2001)
This dissertation studies choral singing within the Christian congregation. In terms of methodology, it analyzes the reality of a congregational choir, compares the results obtained from this study with specific bibliography and returns to the reality with suggestions for working with choirs. The first chapter presents the results of the social research carried out within a congregation, organizing the contents into roles and functions of the congregational choir and into relevant elements for choral work in general. The second chapter starts with this content and develops it into three clear perspectives: that of liturgy, another of the edification of the congregation and the other of music. To do this it makes use of other sciences that are considered related: sociology, anthropology, musical therapy and phonoaudiology. The third chapter, using the impulses gathered from the first chapter and studied in the second chapter, presents, albeit in a way at the present time considered utopic, practical conclusions for choral work in Christian congregations. Work with congregational choirs needs to take into account the musical dimension, being it is dealing with a choir, and the congregational dimension because of the tie with the Christian congregation. For this to happen, within the notion of the body that orients the congregation, it counts on the cooperation of all the people who are part of the congregation.